1045. SORBUS AVONENSIS: Rosaceae. (5th January 2023) - Houston, Libby; Rich, Tim C. G.; Barlow, Gillian; Brown, Andrew P.; Fay, Michael F.
Summary: Sorbus avonensis, AVON WHITEBEAM, is described and illustrated. It was originally treated as a triploid hybrid to cover plants of S. aria (diploid) × S. porrigentiformis (tetraploid) parentage, but after the discovery of more identical trees in 2014–2016, it is now treated as a species. It is endemic to the Avon Gorge, England where a population of c . 47 trees is known.